Analytical comparison of knowledge based traits of DBAs for information visualization in multiple electronic health records - Malik, M.S.A. (WITPress, 2014)
Multiple electronic health records (EHR) have been interactively represented using information visualization (IV) formats for different scenarios. Based on physiciansâ requirements, database professionals develop query sets and perform database operations but they are less involved in the development process of IV tools. Professional use of IV tools is less adapted by physicians due to incompatibility of database administratorâs (DBA) lack of understanding with their end user requirements. Absence of training, poor understanding on IV requirement, and incomplete database knowledge oriented DBA generates incomplete data visualization. The key features with DBA are understanding end user requirements, database management system (DBMS) limitations knowledge, and future improvement perspective from IV point of view. This paper presents the outcome of a survey-based questionnaire study conducted on DBAs and provides an outline of their knowledge factors identification and performance to IV applications. Â© 2014 WIT Press.